MEMPERKUAT KARAKTER SISWA MELALUI PROGRAM GERAKAN RELIGI ISLAMI (GERLIS) - Siti Khatimah; Tomo Djudin; Erlina Erlina (STKIP Persada Khatulistiwa Sintang, 2023)
This research aims to find out how the Islamic Religious Movement (Gerlis) Program can strengthen the character of students at SDN 01 Benua Kayong, Ketapang Regency. By using descriptive qualitative research using a naturalistic approach, the research setting is taken from real conditions. Data collection is done by observing research subjects and objects, conducting interviews and taking the necessary documentation. The research results revealed that the Gerlis program in strengthening student character was implemented through a series of routine activities such as; Morning prayer together in the school yard, the habit of praying before and after learning in class, the creation of a reward corner in class, the reading of Asmaul Husna/Yasin/short Surahs and the habit of donating every Friday morning, the implementation of TPA every after school for grade 1 students and 2, implementation of midday prayers in congregation for students in grades 3 and 4, implementation of midday prayers in congregation, familiarization with 5S (smile, greeting, greeting, politeness), and celebration of Islamic holidays. The conclusion of the research results is that activities to strengthen student character through the Gerlis program include three pathways, first, class-based by integrating KOSP into PABP learning activities, both intra-curricular, co-curricular and extra-curricular. Second, based on school culture by cultivating practices that strengthen religious values through scheduled activities. And third, community-based, involving religious institutions to collaborate in supporting the strengthening of student character.